Skyway builder from skyway software reaching for the sky. - Barbash, Brian (SOA webservices journal.)
Services Oriented Architectures (SOA) rarely start from scratch, in most enterprises, they are built in gradual steps as part of an overall migration and architectural strategy. Along the way, existing legacy systems must be enhanced to support the required interface technologies, service gaps have to be filled by building new systems or acquiring and leveraging external services through third-party providers, and all elements in the architecture must be orchestrated and combined to form the final catalog of services. One solution that helps address these challenges is Skyway Builder from Skyway Software.